Pendidikan Anak Dalam Al Quran - Nasyiatul Aisyah (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2022)
The education of a child is an important thing that every parent must pay attention to. How the patterns and techniques of a good education are basically already in the Quran. This study aims to reveal how the use of the word child in the Quran, apar money in the scope of education, methods and content of education. This research is a literature research, using content analysis. From the study it was concluded that first: in the Quran the word child is expressed five terminologies; ibn, walad, shabiyyun, thiflun, and dzurriyah, second: Children's education is intended to be guidance, maintenance, and nurturing of the potential possessed by the child so that he can grow optimally to achieve educational goals in accordance with the teachings of Islam (Qur'an). The methods of education according to the Qur'an are: exemplary, habituation, advice, deliberation, supervision/attention and stories. And the content or meter of education according to the Qur'an is: aqidah education, moral education, worship education, physical education, ratio education, and social education.